2006
DOI: 10.1093/qjmed/hcl039
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of disease among adults hospitalized with dengue infections

Abstract: Pooling data on adult dengue patients from different regions should help us to understand the natural history of disease in this group. It would also help in developing evidence-based treatment guidelines and allocating limited and scarce health resources. Our data contribute towards this goal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
92
5
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(116 citation statements)
references
References 18 publications
10
92
5
2
Order By: Relevance
“…Similar to the results published in other papers, a higher percentage of women in our study were in their third trimester; and in contrast to a previous Sri Lankan study of dengue in pregnancy [20], our cohort showed that secondary infections were more common than primary (44% versus 62%). This pattern is similar to that of non-pregnant adults [5,29].…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…Similar to the results published in other papers, a higher percentage of women in our study were in their third trimester; and in contrast to a previous Sri Lankan study of dengue in pregnancy [20], our cohort showed that secondary infections were more common than primary (44% versus 62%). This pattern is similar to that of non-pregnant adults [5,29].…”
Section: Resultssupporting
confidence: 81%
“…In general, the most common symptoms include fever, myalgia and arthralgia [5]. Fluid leakage (elevated hematocrit, pleural effusion or ascites) and hemorrhagic manifestations are characteristic features of DHF.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bleeding manifestation was not a common feature in our study, majority of the patients presented with fever, headache, myalgia and generalized rash except four cases who presented with DHF and two cases with DSS which correlates well with other authors [6]. But others had reported higher incidence of bleeding manifestations in their study [7,8]. The major diagnostic methods currently available are viral culture, viral RNA detection by RT-PCR and serological tests such as IgM capture ELISA.…”
Section: Discussionsupporting
confidence: 87%
“…Figure 1 shows the number of DHF cases and deaths since 1989 in Sri Lanka. The occurrence of the massive epidemic in year 2004 is thought to be due to yet another change in the predominant circulating virus serotype (from DEN-2 to DEN-3) 18,19 . DEN-3 was also the cause of the epidemics that occurred in India and other countries of the region during this period 20 .…”
Section: Dengue Viral Infections In Sri Lankamentioning
confidence: 99%